KESESUAIAN LAHAN UNTUK TANAMAN JERUK (Citrus sp.) DAN KOPI ARABIKA (Coffea arabica) DI KECAMATAN SIEMPAT RUBE KABUPATEN PAKPAK BHARAT - Gilbert Fernando Cibro; Purba Marpaung; Mukhlis Mukhlis (Jurnal Agroekoteknologi, 2012)
ABSTRACT The suitability of the land for the plant orange and Arabica coffee (Coffea arabica) in district of Siempat Rube, Pakpak Bharat Regency. A survey of the suitability of the land for the plant orange and Arabica coffee is done in district of Siempat Rube Pakpak Bharat Regency. This study aims to evaluate the suitability of land for the development of citrus fruit and Arabica coffee plant in the Regency of North Sumatra with the altitude of the place is at 800-1400 above sea level. This research was carried out in June 2011 to December 2012. Survey research conducted by taking samples of soil based on the map of the land system in district of Siempat Rube, each land system was taken as many as 10 soil samples taken in a zig-zag, where 10 soil samples and then analyzed the lab and evaluation methods of land made by the method of the limit which refers to the magnitude of the rate limiting factor. The parameters observed in field is soil texture, soil drainage, soil depth, rough material, the dominant vegetation, plant management, soil conservation efforts, the dangers of Flood/inundation, surface rocks and outcrops and the parameters analyzed include the physical properties of dilaboratorium (textures) and chemical properties: cation exchange capacity (CEC) of soils, soil pH, Base Saturation, and the C-organic. The evaluation of land in sub-district siempat rube district pakpak bharat, conformity land potentially for plants orange on class S3-oarc of 334,229 ha,   S2-rceh of 6430,282 ha, S2-rc of 1415,285 ha and S3-rc of 3796,192 ha. Conformity potential land to coffee plant arabica obtained class S3-waoarc of 334,229 ha, S3-wa of 7845,587 ha and S3-warc of 2594,218 ha. Keywords: Evaluation of lands suitability, citrus, arabica coffee.  ABSTRAK Kesesuaian lahan untuk tanaman jeruk (citrus sp.) dan kopi Arabika (Coffea arabica) di Kecamatan Siempat Rube Kabupaten Pakpak Bharat. Survei kesesuaian lahan untuk tanaman jeruk dan kopi arabika dilakukan di Kecamatan Siempat Rube Kabupaten Pakpak Bharat. Penelitian ini bertujuan untuk mengevaluasi kesesuaian lahan untuk pengembangan tanaman jeruk dan tanaman kopi arabika di Kabupaten Pakpak Bharat dengan ketinggian tempat berada pada 800-1400 di atas permukaan laut. Penelitian ini dilaksanakan pada bulan Juni 2011 sampai dengan bulan Desember 2012. Penelitian dilakukan dengan mengambil contoh tanah berdasarkan peta land system di Kecamatan Siempat Rube, setiap land system diambil sebanyak 10 sampel tanah secara zig-zag kemudian di analisis laboratorium dan metode evaluasi lahan dilakukan dengan metode limit yakni mengacu pada besarnya tingkat faktor pembatas. Parameter yang diamati dilapangan adalah tekstur tanah, drainase tanah, bahan kasar, kedalaman tanah,vegetasi dominan, pengelolaan tanaman, upaya konservasi tanah, bahaya banjir/genangan, batuan permukaan dan singkapan batuan dan parameter yang dianalisis dilaboratorium meliputi sifat fisik (tekstur)  dan  sifat kimia: Kapasitas Tukar Kation (KTK) tanah, Kejenuhan Basa, pH tanah,dan C-organik. Hasil evaluasi lahan di Kecamatan Siempat Rube Kabupaten Pakpak Bharat, kesesuaian lahan secara potensial untuk tanaman jeruk pada kelas S3-oarc seluas 334,229 ha, S2-rceh seluas 6430,282 ha, S2-rc seluas 1415,285 ha dan S3-rc seluas 3796,192 ha. Kesesuaian lahan potensial untuk tanaman kopi arabika diperoleh kelas S3-waoarc seluas 334,229 ha, S3-wa seluas 7845,587 ha dan     S3-warc seluas 2594,218 ha. Kata kunci : evaluasi kesesuaian lahan, jeruk, kopi arabika.